Struggle for Liberation of the Peoples of Yugoslavia (Belgrade Operation) - N. F. Azyasskiy (Vestnik MGIMO-Universiteta, 2015)
In the military history of our homeland many memorable important dates leading up to the final victory over fascism are forever imprinted. One of these dates is October 20, 1944, the day of the liberation of Belgrade, the capital of Yugoslavia, and the day of completion of the Belgrade operation. This operation was of special significance for the peoples of Yugoslavia and the Soviet Union. It symbolized the military cooperation of the two countries, which at the most difficult times in their history have always been in the same ranks in the struggle against the common enemy. The Red Army and the People's Liberation Army of Yugoslavia (AVNOJ) were actively joined by the troops of the Fatherland Front of Bulgaria. Given the importance of preserving the memory for the present and future generations an example of joint struggle of our people against the common enemy it is necessary to recall the Belgrade offensive in 1944, as one of the most important events in the history of the World War II. Despite the fact that this topic was thoroughly researched in the Soviet and Yugoslav literature there are still contradictory assessments of combat and the strength of the Soviet Armed Forces groups, groups of interacting forces, the balance of forces involved in the operation. The results of the study of the experience of the offensive in the conditions of the Balkan region can be used for comprehensive training of troops, as the region is a source of international tension, both in Europe and in the world as a whole.